Pemilihan Supplier Suku Cadang Laptop Dengan Menggunakan Metode Analytical Network Process (ANP) (Studi Kasus : Ayyash Komputer) - Dwi Gunawan; Savitri (CV. Multi Kreasi Media, 2023)
Technological developments are increasingly sophisticated in all respects, especially computers and laptops, along with a large number of requests for repairing laptops and purchasing spare parts at the Ayyash Computer shop. So far, they still buy spare parts at random, buy at online stores without any specific criteria, the quality of ordinary goods and do not have a clear price standard. Then a supplier of laptop spare parts is needed to support laptop service activities and the Analytical Network Process (ANP) method is needed, while the specified criteria include quality, price, warranty, and service as well as determining 5 alternative suppliers and assisting in the process of selecting spare parts suppliers laptops for Ayyash Computer shop.